A novel iron (II) tetranitrophthalocyanine/graphene composite as the high-performance catalyst for the oxygen reduction reaction in an alkaline medium. (June 2016) - Yu, Dingling; He, Xingquan
Highlights: The FeTNPc/PSS-rGO are fabricated by an in situ solvothermal approach. The proposed FeTNPc/PSS-rGO exhibits superior ORR performance. The FeTNPc/PSS-rGO are investigated as a potential electrocatalyst for the ORR. Abstract: Developing high-efficiency and low-cost catalysts for the oxygen reduction reaction (ORR) is very important for the large-scale commercialization of direct methanol fuel cells. Here, we successfully synthesized a novel iron (II) tetranitrophthalocyanine/poly(sodium- p -styrenesulfonate) modified reduced graphene oxide (FeTNPc/PSS-rGO) ORR catalyst by a solvothermally assisted π–π assembling method. The FeTNPc/PSS-rGO was characterized by transmission electron microscopy (TEM), ultraviolet–visible (UV–vis) spectroscopy and X-ray photoelectron spectra (XPS). The electrocatalytic properties of the fabricated catalyst toward the ORR were evaluated using the cyclic voltammetry (CV) and linear sweep voltammetry (LSV) methods. Surprisingly, when the mass ratio of FeTNPc to graphene was 1:1, the FeTNPc/PSS-rGO catalyst exhibited superior ORR performance than Pt/C, including more positive onset potential and half-wave potential, better stability and resistance to methanol, favoring a direct 4-electron pathway, which could be used as a promising Pt-free catalyst for the ORR in an alkaline direct methanol fuel cell.